Supraoptimal activity of CHLOROPHYLL DEPHYTYLASE1 results in an increase in tocopherol level in mature arabidopsis seeds. (2nd November 2017) - Lin, Yao-Pin; Charng, Yee-yung
ABSTRACT: Tocopherols are synthesized in photosynthetic organisms, playing a role in plant stress tolerance. Recent studies showed that the phytol moiety of tocopherols comes from the salvaged phytol chain during chlorophyll degradation. However, the enzyme(s) responsible for chlorophyll dephytylation remains unclear. Recently, we reported the identification and characterization of CHLOROPHYLL DEPHYTYLASE1 (CLD1) of Arabidopsis, suggesting its role in chlorophyll turnover at steady state. In this addendum to the report, we presented and discussed the results related to the function of CLD1 in tocopherol biosynthesis. The tocopherol levels in the mature seeds were not altered in the transgenic lines with reduced CLD1 expression but were moderately increased in the plants with supraoptimal CLD1 activity compared to wild type. These results suggest that manipulating CLD1 activity could affect tocopherol biosynthesis to a certain extent and that other dephytylating enzymes are sharing redundant function in contributing the phytol pool in plant cells.